Mecanismos de referenciação nos textos escritos de alunos no Ciclo de Alfabetização - Nogueira, Francisca Nildene (2019)
This work aims to analyze how the process of referencing occurs in written texts produced by students in early literacy processes. For this, we based our research on theoretical contributions about textual production as a discursive and sociocognitive activity and also about the process of referencing as a phenomenon that contributes significantly to textual comprehension and production. We accepted the contributions of Costa Val and Rocha (2008), Heinemann and Viehweger (1991), Mondada (2001), Cavalcante (2011, 2012, 2014, 2017) and Koch (2017). In order to analyze the referential mechanisms that the students use in their written texts, we used forty texts from the Brazilian project MAISPAIC (Programa Aprendizagem na Idade Certa) produced by children from Aracati – CE, who were in their early stages of literacy during 2017. The collection of these texts occurred in Municipal Department of Education of Aracati, which is the institution responsible for the application and analysis the of external evaluations. Our analysis allowed us to verify that, during the referential introduction process, there are many similarities in the way of using referencial expressions in both GI (1st year group) and GII (2nd year group). In the anaphoric process, regarding to the direct anaphora, it is evident, both in the GI and in the GII, a great recurrence of the mechanisms of retake by pronouns, ellipses and by the same noun phrase. As for the encapsulating anaphora, there is aconsiderable use in the GII group. Regarding to the indirect anaphora, in both groups the inferential form was predominant. With respect to the deixis process, the most used types of it, both in GI and GII, were the personal, spatial, temporal (usually marked by verbal tenses in the perfect tense) and the textual deixis. In relation to the other types of dexis, we identified only one occurrence of social dexis in GI and another occurrence of memory deixis in GII. As a result of this work, we identified that children already have a significant knowledge of the referential mechanisms that they can use in the text, since they perform them coherently to fulfill their communicative/enunciative purposes. This activity of textual production reveals in a that children have things to say, an audience and purposes in their own way.